Modalitas Epistemik -Hazu Da dan Padanannya dalam Bahasa Indonesia - Isye Herawati; Fahri Delfariyadi (Universitas Mulawarman, 2023)
Japanese epistemic modality can be expressed through by linguistic markers, such as adverb markers indicate the gradient or level of the speaker’s assumptions about a specific phenomenon. This study aims to investigate the epistemic modality of Japanese -hazu da and its Indonesian equivalent. This study utilized descriptive and qualitative methods, and data were obtained from various novels and Shonagon corpus. The findings of the present study are the adverbs and grammatical components that appear with modal auxiliary verbs, resulting in different epistemic gradations, notably uncertainty in the lowest rank, expectation/reasonable prediction, agreement/consent, disaffirmation, and strong negation, as well as strong affirmation in the highest rank. The Indonesia equivalent derived from this modality are ‘mungkin’, ‘tentunya’, ‘pastinya’, ‘kalau tidak salah’, and ‘mana mungkin’. The speaker’s logical reasoning and assumption supported by the contextual aspect and grammatical items in sentences.